2020
DOI: 10.1002/ep.13514
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nickel oxide nano‐additives in Azadirachta indica biodiesel‐diesel blend on engine performance and emission characteristics by varying compression ratio

Abstract: The utilization of biodiesel‐diesel blends in compression ignition (CI) engines are a viable option for the current energy crises. But due to better combustion features of biodiesel‐diesel blends leading to high NOx release from engine exhaust hinders the use of such blends. Usually all of the harmful exhaust emissions like HC and CO reduces marginally, except nitrogen oxides at higher compression ratios with biodiesel blended fuel. The present paper focuses on the study of variation of compression ratio and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Also, the amount of variance in BSFC between Diesel RK and experimental was 15.6%, 14.9%, 15.1%, and 13.9% for conventional diesel, B20, B40, and B100 biodiesel blends. The results were in line with the findings done by Al-Dawody 27 and Campli et al 28…”
Section: Fuel Consumption Studiessupporting
confidence: 93%
“…Also, the amount of variance in BSFC between Diesel RK and experimental was 15.6%, 14.9%, 15.1%, and 13.9% for conventional diesel, B20, B40, and B100 biodiesel blends. The results were in line with the findings done by Al-Dawody 27 and Campli et al 28…”
Section: Fuel Consumption Studiessupporting
confidence: 93%
“…At full load D80B10RW10, D70B20RW10, and D60B30RW10 gives 1.46%, 2.86%, and 3.91% lower Bthe than diesel, this is due to low‐calorific value of biodiesel and rice wine alcohol 38 . In general, Bthe decreased as mass flow rate increased because Bthe is inversely proportional to mass flow rate and calorific value, correlating this factor, Bthe mainly depend on mass flow rate because calorific value is fixed for particular fuels, where diesel‐biodiesel‐alcohol blend mass flow rate is found high as compared to diesel 42 to produce certain brake power, as brake power is constant for all fuels at particular load 14,31 therefore, it is known that higher blends of biodiesel gives low Bthe 56,57,62 due to low‐calorific value, low volatility, and high‐latent heat compared to low blend of biodiesel and diesel. But still all blended fuels have a closer value of Bthe to diesel this might be due to 10% rice wine alcohol that helps oxidation process and faster flame propagation for better performance of an engine.…”
Section: Resultsmentioning
confidence: 94%
“…[6][7][8][9][10][11] Moreover, it is evident from literature and concluded from a detailed study that nano-catalysts provide better conversion and yield for biodiesel conversion than conventional heterogeneous catalysts with better optimum conditions. [12][13][14][15][16][17] The studies have also revealed that the additive with biodiesel fuel mixtures augments the engine combustion characteristics and reduces the emissions; moreover due to nano-catalytic effects, raised CO 2 emissions and minimal O 2 emissions are also pellucid from studies made on biodiesels obtained from high FFA oils using inorganic nano-catalysts. 1,18 A concise overview of several nano-catalysts used so far for production of biodiesel has been tabulated in Table 1.…”
Section: Introductionmentioning
confidence: 99%